Pemanfaatan Limbah Sayur Sebagai Desain Ecoprint Pada Totebag Untuk Anak Sanggar Yatim Kutilang Tembung - Cut Latifah Azhari; Putri Ramauli Hutasoit; Rahmi Diah; Ratna Sari Sitompul; Resi Febrina Nainggolan; Rika Mawarni; Rima Rizky Melati (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
pollution while providing added value through artistic approaches. This community engagement project aimed to educate and train children at the Kutilang Tembung Orphanage Studio to utilize vegetable scraps as the main material in ecoprint techniques applied to totebags. The method included awareness sessions on recycling, demonstrations of the ecoprint process, and hands-on activities where children printed vegetable waste such as mustard greens and pakcoy onto canvas totebags using acrylic paint. The results showed increased understanding of waste management, enhanced creativity, and improvement in children's fine motor skills. Participants displayed high enthusiasm, joy in expressing themselves artistically, and pride in their finished products. Beyond the artistic experience, this activity instilled important values related to environmental conservation and sustainable living from an early age. In conclusion, the ecoprint program effectively empowered children through environmentally themed art and introduced the concept of a circular economy within the community setting.